Vaccinations for migrants during and beyond the COVID-19 pandemic. (20th October 2021) - Declich, S; Dente, MG; Tosti, ME; De Ponte, G; Marchetti, G; Tavoschi, L; Lopalco, PL; Russo, ML; Marceca, M
Abstract: Issue: Migrants have suboptimal vaccination coverage compared to the general population in destination countries due to several factors -administrative barriers or lack of legal entitlements to health -health system barriers (language, lack of cultural sensitivity and community engagement capacity, vaccination costs) -lack of trust in the health system and misconceptions about vaccines due to misinformation or beliefs Problem: Countries should develop national policies and ensure an inclusive, free of charge and proactive vaccination offer to migrants, irrespective of their legal status; and to extend this approach beyond the current pandemic and the sole COVID-19 vaccine Results: To achieve COVID-19 global herd immunity all population groups, including migrants, needs to access vaccination. Tailored vaccination strategies, once devised, shall be applied to routine national vaccination plan to tackle health inequalities Lessons: The following actions shall be implemented at national level Action 1. Develop tailored and equitable approaches for PH vaccination services targeting migrants through: -free of charge access -decentralization and outreach capacity of the health system -innovative service delivery models (mobile clinics, combined health services, mass vaccination) -health personnel and migrants participatory approach and engagement strategies Action 2. Increase staff engagement through: -increasing health personnel's difference sensitivity -strengthening health personnel's communication capacities Action 3. Increase migrants' health and vaccine literacy through: -establishing vaccine literacy education programmes and strategies -offering health promotion educational interventions Action 4. Monitor progress of inclusive vaccination offer by: -setting strategic goals, targets and indicators for national vaccination plans -expanding immunization information systems to monitor vaccination coverage, with appropriate disaggregation by migration status core variables Key messages: Explicitly and proactively include migrants and displaced communities in vaccination plans and set up, test and implement new approaches in primary prevention and vaccination services. Extend this approach beyond the current pandemic and the sole COVID-19 vaccine in order to enhance preparedness to present and future health threats.